2020
DOI: 10.1039/c9nh00693a
|View full text |Cite
|
Sign up to set email alerts
|

A simple yet effective AIE-based fluorescent nano-thermometer for temperature mapping in living cells using fluorescence lifetime imaging microscopy

Abstract: A novel nano-thermometer composed of butter and AIE molecules can be used for intracellular temperature mapping using fluorescence lifetime imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 41 publications
0
46
0
2
Order By: Relevance
“…The emission lifetime is a non-extensive and specific property of each compound, allowing discrimination between the emission from the cell components and the luminescent label [ 117 , 118 ]. Cell components and organic dyes usually show emission lifetimes in the nanoseconds range, Table 2 , which makes Fluorescence Lifetime Imaging Microscopy (FLIM) one of the most used techniques [ 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Although FLIM is a technique that allows us to discriminate between the emission lifetimes of the cell components and luminescent labels, there is not complete elimination of the cell emission from the image.…”
Section: Luminescence Imagingmentioning
confidence: 99%
“…The emission lifetime is a non-extensive and specific property of each compound, allowing discrimination between the emission from the cell components and the luminescent label [ 117 , 118 ]. Cell components and organic dyes usually show emission lifetimes in the nanoseconds range, Table 2 , which makes Fluorescence Lifetime Imaging Microscopy (FLIM) one of the most used techniques [ 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Although FLIM is a technique that allows us to discriminate between the emission lifetimes of the cell components and luminescent labels, there is not complete elimination of the cell emission from the image.…”
Section: Luminescence Imagingmentioning
confidence: 99%
“…[ 5–18 ] For the last few decades, a series of fluorescent nanomaterials, such as semiconductor quantum dots, organic dyes, fluorescent polymers, and metal nanoclusters (NCs) have been developed as typical fluorescence‐based sensors for temperature detection. [ 19–25 ] They work based on temperature‐dependent luminescence intensity and/or decay time. [ 26,27 ] However, the above materials possess obviously unavoidable disadvantages, such as low sensitivity, systematic errors, biotoxicity, environmental pollution, and unstable optical characteristics at different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They show the following advantages: high optical absorptivity, adjustable fluorescent emission, chemical stability, well biocompatibility, and low toxicity. [ 5–99 ] Given these superior properties, they have been extensively discussed in bioimaging devices, biosensors, catalysts, photovoltaic devices, as well as fluorescent nanothermometers for spatially resolved temperature ( Figure ). [ …”
Section: Introductionmentioning
confidence: 99%
“…Temperature influences the equilibrium constants and biochemical reaction kinetics in fundamental cell processes, including enzyme activity, gene expression, cell division and energy metabolism [1][2][3][4]. In cases of diseases such as cancer, pathological studies have revealed that malignant cells in tissues change their metabolic activities, leading to acute deviation of the intracellular temperatures from the normal state [1][2][3][4]. Furthermore, accurate information on the local temperature profile is also relevant in carrying out therapeutic treatments, such as phototherapy, for the selective and local killing of diseased cells, to avoid unwanted destruction of the healthy tissue surrounding the treated area.…”
mentioning
confidence: 99%
“…Different types of nanothermometers [7][8][9][10][11][12] have been developed that offer a direct read-out of the temperature by transducing a temperature-dependent change of an optical property of the selected material, such as absorption, emission or Raman scattering. In this regards, fluorescent nanoparticles (NPs), such as quantum dots (QDs) [9,13,14], luminescent semiconductor [15], carbon dots [12,16], rare earth doped up-converting or down-converting NPs [1,7,8,17,18], polymeric particles [2,3,11,19] or organic dyes [10] are emerging as promising luminescence nanothermometry devices. They take advantage of the thermally induced changes of a fluorescence characteristic such as band intensity, band shape, spectral position and lifetime for a precise, and often multiparametric and ratiometric, [3,7,9,10,20] temperature detection.…”
mentioning
confidence: 99%